Prevalence study of yaws in the Democratic Republic of Congo using the lot quality assurance sampling method. - Sibylle Gerstl; Gédeon Kiwila; Mehul Dhorda; Sylvaine Lonlas; Mark Myatt; Benoît Kebela Ilunga; Denis Lemasson; Elisabeth Szumilin; Philippe J Guerin; Laurent Ferradini (PLoS ONE, 2009)
BACKGROUND:Until the 1970s the prevalence of non-venereal trepanomatosis, including yaws, was greatly reduced after worldwide mass treatment. In 2005, cases were again reported in the Democratic Republic of the Congo. We carried out a survey to estimate the village-level prevalence of yaws in the region of Equator in the north of the country in order to define appropriate strategies to effectively treat the affected population. METHODOLOGY/PRINCIPAL FINDINGS:We designed a community-based survey using the Lot Quality Assurance Sampling method to classify the prevalence of active yaws in 14 groups of villages (lots). The classification into high, moderate, or low yaws prevalence corresponded to World Health Organization prevalence thresholds for identifying appropriate operational treatment strategies. Active yaws cases were defined by suggestive clinical signs and positive rapid plasma reagin and Treponema pallidum hemagglutination serological tests. The overall prevalence in the study area was 4.7% (95% confidence interval: 3.4-6.0). Two of 14 lots had high prevalence (>10%), three moderate prevalence (5-10%) and nine low prevalence (<5%.). CONCLUSIONS/SIGNIFICANCE:Although yaws is no longer a World Health Organization priority disease, the presence of yaws in a region where it was supposed to be eradicated demonstrates the importance of continued surveillance and control efforts. Yaws should remain a public health priority in countries where previously it was known to be endemic. The integration of sensitive surveillance systems together with free access to effective treatment is recommended. As a consequence of our study results, more than 16,000 people received free treatment against yaws.